2017
DOI: 10.21037/jgo.2017.08.15
|View full text |Cite
|
Sign up to set email alerts
|

The correlations between serum amphiregulin and other clinicopathological factors in colorectal cancer

Abstract: High serum AREG was associated with advanced diseases and poor pathologic factors in CRC. It is potentially a prognostic marker in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…AREG, a member of the EGF family, was reported as having high expression in CRC and was associated with tumor invasion, liver metastasis, and lower survival 33 . Recently, serum levels of AREG higher than 25 pg/mL, evaluated in 120 CRC patients, was significantly associated with liver and peritoneal metastasis 34 . The authors also found high levels of serum AREG associated with distant metastasis, mucinous histological grade, lymphovascular and perineural invasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AREG, a member of the EGF family, was reported as having high expression in CRC and was associated with tumor invasion, liver metastasis, and lower survival 33 . Recently, serum levels of AREG higher than 25 pg/mL, evaluated in 120 CRC patients, was significantly associated with liver and peritoneal metastasis 34 . The authors also found high levels of serum AREG associated with distant metastasis, mucinous histological grade, lymphovascular and perineural invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found high levels of serum AREG associated with distant metastasis, mucinous histological grade, lymphovascular and perineural invasion. In serum from rectal cancer (N = 53) patients, high expression of AREG was detected in 24.5% of cases 34 . In our sample set, two cases presented high levels of AREG (10 and 12 pg/mL) and none of them presented distant metastasis or other clinical pathological features as described by Chayangsu et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings underline the potential dual role of the IL-33/ST2 axis in colon cancer (63) and the need for further analysis of this pathway in different CRC models. AREG is another important molecule that regulates cancer cell proliferation, invasion and angiogenesis (64) and has been proposed as a prognostic marker in CRC (65). AREG upregulation is associated with increased migration and invasion of CRC cells which is essential for metastasis [(66, 67); Figure 1, left middle panel].…”
Section: Ilc2s In Cancers Of the Gastrointestinal Systemmentioning
confidence: 99%
“…EGFR ligands, epiregulin (EREG) and amphiregulin (AREG) are overexpressed in CRC [30,31] . EREG and AREG expressions in mRNA, tumor protein and plasma protein levels are associated with poor prognosis in CRC [31][32][33] . In vitro studies demonstrated their autocrine activation and reduction of cetuximab effect in AREG and EREG gene silencing CRC cells [34,35] .…”
Section: Other Biomarkersmentioning
confidence: 99%